HUBUNGAN PENGETAHUAN DAN STATUS EKONOMI IBU HAMIL DENGAN KEJADIAN KEKURANGAN ENERGI KRONIK (KEK) PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS RIMBO KEDUI KABUPATEN SELUMA - WAYTHERLIS APRIANI (STIKes CHMK, 2022)
The low coverage of immunization cannot be separated from the factors that influence immunization, namely health behavior. This study aims to determine the relationship between knowledge and economic status with the incidence of chronic energy deficiency (KEK) in pregnant women in the working area of Puskesmas Rimbo Kedui, Seluma Regency. The design of the study used an analytic survey with a cross sectional approach. The population in this study were all pregnant women in the Work Area of the Rimbo Kedui Public Health Center, Seluma Regency from 29 July to 31 August 2020 as many as 31 people who were taken in total sampling. Data collection, namely primary and secondary data. The analysis technique used univariate and bivariate (Chi square). The results obtained: from 31 mothers there were 21 mothers (67.7%) who did not experience KEK, 13 mothers (41.9%) had good knowledge, 17 mothers (54.8%) had sufficient economic status. There is a relationship between knowledge and economic status with the incidence of Chronic Energy Deficiency (KEK) in pregnant women in the working area of the Rimbo Kedui Public Health Center, Seluma Regency. It is hoped that health workers in carrying out coaching tasks in the immunization program, especially the advanced rubella measles immunization, can be done by forming community cadres in approaching pregnant women, postpartum and mothers with babies Keywords: KEK, Knowledge, Economic Status